PERSEPSI MAHASISWA TERHADAP PERILAKU MEROKOK DI KAMPUS TERPADU POLITEKNIK KESEHATAN KEMENKES NANGGROE ACEH DARUSSALAM - , Intan Liana; , Dra. Yayi Suryo Prabandari, M.Si., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The emergence of smoking behavior in adolescents is affected not only by family condition but also by environmental factors, such as physical, biological and socio-cultural factors which in turn influence the degree of health either directly or indirectly. Smoking habits of family members and influence of peer friends may affect adolescents to behave the same. Objective: This study was aimed to obtain an overview of smoking behavior and the correlation between studentâs perceptions (vulnerability, threat, benefits and barriers) and smoking behavior in the integrated campus of Nanggroe Aceh Darussalam (NAD) Health Polytechnic. Method: This was an analytical-observational study with a cross-sectional study design. This study was to identify perceptions on smoking behavior among students by using structured questionnaires. The sample size was the total population as many as 226 respondents. The data analysis comprised bivariable analysis using chi-square test, ttest and Anova and multivariable analysis using multiple logistic regresion, with significance level p <0.05. Result: Smoking behavior among NAD Health Polytechnic students presented proportion that 65.49% of the male students were smokers (48% regular smokers and 18% experimental smokers). There was a correlation between perceptions on vulnerability and threats against smoking and smoking behavior. There was no significant correlation between perception on barriers and benefits of not smoking and smoking behavior. There was a significant correlation between perceptions of vulnerability and threat and smoking behavior. Prevalence of smoking among college students was greater in students who had negative perception (vulnerability) 2.8 times than those with positive perception. Prevalence of smoking in students with negative perception (threat) was five times greater than those with positive perception. The multivariable analysis selected was Model 1, with the variables of vulnerability and threat having a significant correlation. Conclusion: Students with negative perceptions on vulnerability and threat can cause them to become smokers